Diagnosis of Hanging in an Alleged Case of Ligature Strangulation: A Case Report - Sharma , N; Giri , S; Khanna , K; Dagar , T; Pal, V (Journal of Indian Academy of Forensic Medicine, 2023)
Hanging is one of the commonest method among the painless suicidal deaths. In few instances, false allegations are made by next of kin and they claim that the ligature mark over the neck of deceased is due to strangulation or postmortem hanging rather than ante-mortem hanging. Vice versa cases are also likely in an attempt to concealment of the crime. In such cases, complete post-mortem examination and incident scene visit are very helpful to differentiate between the two. In the case being reported, the authors report a case of young adult female individual in which ligature strangulation was alleged by the parents and investigating officer but which was diagnosed as a hanging after autopsy. Authors also report the important external as well as internal findings in a case of hanging and discuss the unusual complications lead to death after hanging.